Kristus Kosmis Menurut Pierre Teilhard de Chardin - Haward, Ambrosius S. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2022)
Science and theology are often confronted each other since these two disciplines have developed their respective methods. The first is based on empirical research, while the later is based on faith reflection. At the same time, it seems difficult to find theological reflection which bases its reflection on scientific invention. Among a few theologians who base their theological reflection on scientific invention is Pierre Teilhard de Chardin. This article, by way of a literature research, explains Teilhard’s reflection on Christology based on his view of evolution theory. In this article, the author combines Teilhard’s writings about Christological reflection and other theologians’ writings exploring Teilhard’s thoughts. Teilhard was influenced by Henri Bergson’s view of evolution. Nevertheless, quite different from Bergson’s view about evolution as an aimless movement, Teilhard, on the contrary, sees the evolution as a process with a definite purpose to the Omega point. The Omega point is another name of Christ, as the apex of the evolution of all creation.